DEVELOPMENT OF THE INSTITUTIONAL TRAPS THEORY IN UKRAINIAN RETAIL BUSINESS - О. Є. Мазур (Ринкова економіка: сучасна теорія і практика управління, 2016)
The retail trade is the most active segment in Ukrainian trade structure. However the positive dynamics of the trade sector hides a deep strain of an institutional nature. The aim of the article is the continuation of the institutional traps theory’s development in Ukrainian retail trade, namely, the further identification and description of a number of inefficient rules and regulations which have grown into traps and hinder the upward industry’s development. The article presents the author’s interpretation of the institutional trap and identifies a number of traps inherent to Ukrainian retail trade sector. The following traps are described: the trap of street trading, the trap of consumer rights’ violation, the trap of short-term strategies, the tax evasion trap, the trap of salaries in envelopes (a kind of tax evasion trap) and the corruption trap. The fundamental causes of institutional traps formation in the retail trade are determined. It is pointed that the traps are capable of growing stronger because of the pathological incapability of the government to implement the truly systemic, rather than imitating, institutional reforms. Further scientific research on the topic of study should be related to the search of underlying causes and of institutional traps functioning mechanisms identified on the basis of a detailed theoretical and empirical analysis. It is possible, for example, in the course of the field sociological research for the study of contractors’ motivation which prefer to observe objectively inefficient rules of conduct.